Niveles de ceniza y su efecto en la propagación vegetativa del Bambusoideae sp (Bambú amarillo) en Zungarococha 2022 - Tineo Lopez, Alejandra (2025)
The work was developed with responsibility and with the ethical values that all investigator should have, the cultivation settled in the I am founded of Zungarococha, using you bamboo stakes (it leaves he/she mediates) and evaluating longitude radicular, taken root plants, leaves and prendimiento percentage, the population conformed it 480 stakes of the mentioned cultivation installed in 12 beds of 10 m2 c/u and 40 stakes settled down in them, to calculate the field data the DBCA you/he/she was used with (4 methods AND 3 reproductions) and the SOFTWARE INFOSTAD, being reached the following conclusions: It is viable the propagation of the Bamboo for vegetative means (you stake) and using organic payment (wooden ash) especially Treatment 3 (4 kg/m2 of ash) for the registered satisfactory values, also for their express vegetative development and speed of natural regeneration is a species that he/she would help to mitigate the adverse effect of the climatic change; since for hectare it can be able to accumulate during their first five years up to 150 Tons of Carbon and it is a cultivation that can be used also in the cattle feeding, in the constructions of houses and I eat environmental service that ready to the humanity.